VERBOSITIES PRODUCED BY NEW SPEAKERS OF ENGLISH IN TIK TOK THROUGH UNCLE CLINTON’S SPACE CHANNEL - Amran, Ali (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
This qualitative research tries to investigate and list the number of verbosities (using or containing too many words, full of words) which is regarded redundant in terms of structure, semantic point of views, that produced by the followers in social media called Tik-tok.  Tik-Tok now is one of the massive communication activities that followed by thousands even hundred million followers worldwide at the same time. Uncle Clinton’s Space Channel is one of the channels which followers may freely join, ask and answer questions in this channel. They are also free to propose and response the questions and share some information about their hobbies, talents, their working experiences, new knowledge and so on. Also, in this unique channel, the researcher prepares and offers various interesting topics to the followers to discuss. The targets of this channel for the followers are to listen, to understand then to response each topic proposed. Through listening, understanding and responding those topics the followers produce many verbosities, words, like; little-little, more cheaper, more bigger, expensive price, cheap price, sharing-sharing, more better, expensive price, more easy, more good, I am agree, I am disagree, I am understand and so on, which are grammatically non-standard English. In this case the researcher wants to clarify why a number of verbosities appear and why they produce them when they are speaking